PENGELOLAAN KEUANGAN PENDAPATAN ASLI DAERAH (PAD) DALAM MENJAGA TINGKAT RASIO KEMANDIRIAN DAERAH DI KOTA CILEGON TAHUN 2018-2020 - Sapitri Sapitri; Khaerul Umam; Abdal Abdal (Universitas Bina Taruna Gorontalo, 2022)
This study aims to determine the financial management of Regional Original Income (PAD) in Maintaining the Ratio of Regional Independence of Cilegon City in 2018-2020. This study uses secondary data obtained from the Regional FinancialManagement Agency (BPKAD), as the regional apparatus authorized to manage regional finances ofCilegon City. The theory used by Baldric Siregar consists of Financial Planning, Financial Implementation, and Financial Reporting using the Halim formula, namely the Regional Financial Independence Ratio, Effectiveness Ratio, and Efficiency Ratio. The results of the study concluded that the City of Cilegon uses an information system to facilitate the implementation and reporting of PAD regional finance, although Cilegon City still relies on transfer funds (both from the Provincial Government and Central Government), but has made efforts to increase regional independence based on the average percentage growth PAD is 39.41%. Based on the effectiveness ratio, So it can be concluded that the financial performance of the Cilegon City Government for 3 years (2018-2020) is quite good even though it fluctuates per year.